REPRESENTASI BENTUK KALIMAT PADA TUTURAN ANAK USIA 4 TAHUN - Asri Ismail; Muhammad Saleh; Renold Renold (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Sentence Form Representation in Speech of 4-Year-Old. Children This research aims to describe interrogative, declarative, and imperative sentence forms in 4 year-old children using descriptive research. The subject in this study was a 4-year-old boy named Ahmad Fauzan, called Fauzan. Fauzan was born in Bila Village, Amali District, Bone Regency. The method of data collection is done by recording, observing, and taking notes. The data analysis stage in this study went through three stages: (1) reduction, (2) presentation, and (3) drawing conclusions. The results of his research found 2 interrogative sentences, 5 declarative sentences, and 4 imperative sentences.